A unified view on planning, scheduling and dispatching for a factory. (October 2020) - Wu, Kan; Shen, Yichi
Abstract: In a smart factory, the decisions of planning, scheduling and dispatching are made based on the real time information through Internet-of-Things. To ensure the organization objective can be carried out through different levels faithfully, planning, scheduling and dispatching should be considered through a cyber physical production system in an integrated manner. To support the implementation of a smart factory, their definitions have to be given through a unified view. The distinction between planning and scheduling is given based on microeconomics and queueing theory. The distinction between scheduling and dispatching is analyzed from the viewpoint of computational complexity and hierarchical decomposition. Based on the elasticity of price and capacity, planning can be separated into demand planning or capacity planning. Scheduling period is the time horizon where price and average production costs are insensitive to the production rate. The critical roles of the master production schedule and throughput targets in job scheduling have been explained through the concept of hierarchical decomposition. Dispatching is the last layer of scheduling in the hierarchical decomposition.